Sistem Informasi Geografis Pemetaan Lokasi Izin Dokter Praktik Di Kota Medan - Maliha Anjely Putri Sinaga; Muhammad Irwan Padli Nasution; Septiana Dewi Andriana (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Practicing doctors in Medan City obtain permits through the Medan City Investment and One Stop Integrated Service Office (DPMPTSP). The information contained in the institution is still in tabular form and does not provide a clear geographical description of the location of the licensed doctor. So, we need a geographic information system regarding the location of the doctor's license to practice with a special location, namely Medan City. This study uses Leaflet for map visualization and also GeoJSON as a format for encoding geographic data structures. With this system, it can provide information about practicing doctors to the public about the distribution of practicing doctors in the city of Medan and can help facilitate the activities of the Medan City DPMPTSP in monitoring the location of practicing doctors who have permits.